2022
DOI: 10.3390/genes13020290
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants in IL6 Gene (rs1800795) with the Concentration of Inflammatory Markers (IL-6, hs-CRP) and Superoxide Dismutase in the Blood of Patients with Acute Pancreatitis—Preliminary Findings

Abstract: In the course of acute pancreatitis, interleukin-6 plays an important role as a mediator in the inflammatory response. The course of inflammatory disease is associated with intensive oxidative stress, which may activate transcription factors leading to gene-expression changes. Isoenzymes of superoxide dismutase are involved in the defense against free radicals. This study aimed to evaluate changes in IL-6 concentration and the concentration/activity of superoxide dismutase isoenzymes (SOD1, SOD2, and SOD3) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The reason why people from control group higher concentrations of IL-6 may also be that the of erythrocytes from this group showed statistically signi cant higher concentration of cadmium compared to the diabetic group, which would indicate that people in this group accumulate cadmium which has a pro-in ammatory effect. Ołdakowska et al (49) showed a increase in IL-6 concentration in smokers compared to non-smokers in the group of patients with acute pancreatitis. In addition, there were more in control group and in the obese group than in the diabetic group.…”
Section: Discussionmentioning
confidence: 97%
“…The reason why people from control group higher concentrations of IL-6 may also be that the of erythrocytes from this group showed statistically signi cant higher concentration of cadmium compared to the diabetic group, which would indicate that people in this group accumulate cadmium which has a pro-in ammatory effect. Ołdakowska et al (49) showed a increase in IL-6 concentration in smokers compared to non-smokers in the group of patients with acute pancreatitis. In addition, there were more in control group and in the obese group than in the diabetic group.…”
Section: Discussionmentioning
confidence: 97%
“…Te reason why people from the control group had higher concentrations of IL-6 may also be that the lysate of erythrocytes from this group showed a statistically signifcant higher concentration of cadmium compared to the diabetic group, which would indicate that people in this group accumulate cadmium which has a proinfammatory efect. Ołdakowska et al [50] showed a 1.5-fold increase in IL-6 concentration in smokers compared to nonsmokers in the group of patients with acute pancreatitis. In addition, there were more smokers in the control group and in the obese group than in the diabetic group.…”
Section: Discussionmentioning
confidence: 97%
“…However, the pancreatitis activity scoring system (PASS), recently developed by several pancreatitis experts, has been shown to be useful in the assessment of MSAP 5 , although there are few clinical studies of it. Given that AP is accompanied by a significant systemic inflammatory response 6 , we investigated the value of serum CRP and IL-6 assay combined with PASS in assessing the severity of AP patients.…”
Section: Introductionmentioning
confidence: 99%